Buck-boost converter Fed nine level cascaded H-bridge inverter - Devendiren, Shobana; Babu, R. Samuel Rajesh; Ramamurthi, Subbulakshmy (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
This research investigates on simulation of a traditional cascaded H-bridge (CHB) five-level inverter and proposes a nine-level cascaded H-bridge inverter system. The performance of both five-level and nine-level inverter systems is evaluated by modeling and simulating the open-loop system. According to the simulation results, the nine-level multilevel inverter (MLI) has a lower total harmonic distortion (THD) than the five-level MLI. The work also introduces a boost converter positioned between a photovoltaic power source and the inverter. A nine-level inverter system is utilized to simulate the proposed photovoltaic and battery-based buck-boost converter (BBC). The effectiveness of the proposed inverter is verified through simulation studies under various scenarios. In terms of THD, the comparison of the open-loop systems indicates that the nine-level inverter performs better than the five-level inverter. Additionally, simulations for a battery-based buck-boost converter and photovoltaic system used to verify the effectiveness of the proposed inverter.